The dicyclen–TPE zinc complex as a novel fluorescent ensemble for nanomolar pyrophosphate sensing in 100% aqueous solution. Issue 11 (5th November 2014) - Xu, Hao-Ran; Li, Kun; Wang, Ming-Qi; Wang, Bo-Lin; Wang, Xin; Yu, Xiao-Qi
Abstract : Dicyclen–TPE conjugates were developed as novel fluorescent chemosensors for PPi sensing, which could selectively respond to PPi over other phosphate-based anions in 100% aqueous medium with a detection limit of 22.8 nm. Abstract : A dicyclen–TPE Zn(ii ) complex was developed as a fluorescent ensemble for pyrophosphate (PPi) in water. The complex was characterized by X-ray single crystal diffraction, which could selectively respond to PPi over other phosphates with a large enhancement of fluorescence intensity, and the detection limit was determined to be 22.8 nM.